School-Based Curriculum in China Conceptions and Practices to Unleash School Vitality - Cui, Yunhuo; Lei, Hao.; Zhou, Wenye; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book first develops a framework to understand the curriculum administration system in China. It describes the historical process of localizing school-based curricula as well as the significance and positioning of school-based curricula, and presents in detail cases of how three types of school-based curriculum were developed and implemented in Chinese schools. The book outlines for the first time best practices in school-based curriculum development in China, i.e. how to make a holistic curriculum plan, how to design a curriculum, and how to develop a course in the context of a school-based curriculum. By discussing these three aspects, it clearly summarizes the strategies and technologies for school-based curriculum development, which are applicable across contexts. Although the concept originated outside China, school-based curriculum development in China differs from that in other countries both in theory and practice. This book equips readers with theoretical and practical knowledge of how to develop school-based curricula and how to generate experiences for new curriculum development. This timely book is a valuable resource for researchers, curriculum designers, school teachers and others who are interested in school-based curriculum development.
Part I Conceptualizations and Contexts -- Chapter 1 K-12 Curriculum Management System in China -- 1.1 Curriculum management: Theories, traditions, and trends -- 1.2 Curriculum management in China: From the centralized to the decentralized -- 1.3 Frame of three-level curriculum management: Rights and responsibilities divided among the national, regional and school levels -- Chapter 2 Localized Development of School-based Curriculum -- 2.1 School-based curriculum as teaching subjects -- 2.2 Introduction and localization of School-based curriculum as a foreign concept -- 2.3 Role of School-based Curriculum in the National Curriculum Plan -- Chapter 3 Positioning and Significance of School-based Curriculum -- 3.1 Positioning of school-based curriculum in the Primary and Junior High School Curriculum Plan -- 3.2 Positioning of school-based curriculum in the Senior High School Curriculum Plan -- 3.3 Values and significance of school-based curriculum to students, teachers and schools -- Part II Cases and Best Practices -- Chapter 4 To Design a Course under School-based Curriculum -- 4.1 Operations and procedures -- 4.2 Case I: Course of Zhoushan Sculpture -- Chapter 5 To Plan a Cluster under School-based Curriculum -- 5.1 Operations and procedures -- 5.2 Case II: TBC -- Chapter 6 To Develop a System of School-based Curriculum in a School -- 6.1 Operations and procedures -- 6.2 Case III: Affiliated Primary School to East China Science and Technology University in Shanghai -- Coda: Challenges and Prospects of School-based Curriculum in China.
Keywords: Curriculums (Courses of study).; Education$1 (BCurricula.s; Learning; Instruction; Educational policy; Education and state; Curriculum Studies; Learning & Instruction; Educational Policy and Politics